SPARK: A Transcriptional Assay for Recording Protein‐Protein Interactions in a Defined Time Window. Issue 7 (14th July 2021) - Geng, Lequn; Kroning, Kayla E.; Wang, Wenjing
Abstract: Protein‐protein interactions (PPIs) are ubiquitously involved in cellular processes such as gene expression, enzymatic catalysis, and signal transduction. To study dynamic PPIs, real‐time methods such as Förster resonance energy transfer and bioluminescence resonance energy transfer can provide high temporal resolution, but they only allow PPI detection in a limited area at a time and do not permit post‐PPI analysis or manipulation of the cells. Integration methods such as the yeast two‐hybrid system and split protein systems integrate PPI signals over time and allow subsequent analysis, but they lose information on dynamics. To address some of these limitations, an assay named SPARK (S pecific P rotein A ssociation tool giving transcriptional R eadout with rapid K inetics) has recently been published. Similar to many existing integrators, SPARK converts PPIs into a transcriptional signal. SPARK, however, also adds blue light as a co‐stimulus to achieve temporal gating; SPARK only records PPIs during light stimulation. Here, we describe the procedures for using SPARK assays to study a dynamic PPI of interest, including designing DNA constructs and optimization in HEK293T/17 cell cultures. These protocols are generally applicable to various PPI partners and can be used in different biological contexts. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Designing DNA constructs for SPARK Basic Protocol 2 : Performing the SPARK assay in HEK293T/17 cell cultures Support Protocol 1 : Lentivirus preparation Support Protocol 2 : Immunostaining of SPARK components